Essential recycling and repurposing of food waste for environment and sustainability - Rai, Navneet; Pavankumar, Theetha L.; Ghotra, Baljit; Dhillon, Simarata; Juneja, Vijay; Amaly, Noha; Pandey, Pramod (Frontiers in Sustainable Food Systems, 2025)
Food waste valorization by recycling and repurposing is critical for lowering the environmental and economic burden of discarded food and facilitating the transition to a circular economy. Several research have focused on recycling technology and end-use products; nonetheless, their economic, environmental, and social impacts are limited. This study employs an integrative review approach to analyze global challenges related to food waste and develop a comprehensive single-source reference on this critical issue. Food supply chain activities, including retail and consumption, microbial and food safety concerns, and greenhouse gas (GHG) emissions in the context of food waste, were evaluated. Despite significant efforts to overcome these challenges, approximately 1.3 billion tons of edible food are lost or wasted annually, leading to the emission of around 3.3 billion tons of greenhouse gases. The environmental impact, ranging from 347 to 2,969 kg CO₂ equivalent per ton of food waste, depends on multiple factors within food supply chains and waste management systems. This review focuses on the following challenges: (1) stress on croplands related to food production and its consequential impacts; (2) limitations of croplands, food production constraints, and waste generation trends at various stages of supply chains; (3) existing strategies for controlling waste by sources and categories, along with the detrimental economic impacts of food waste; and (4) currently available technologies for waste treatment and conversion into value-added products. Overall, food waste is primarily used for energy recovery, biofertilizers, and biomaterials. However, innovative food waste conversion strategies have the potential to create high-value products, foster industrial collaboration, and further support the circular economy.